Advanced mobility and transport engineering - Hammadi, Slim.; Ksouri, Mekki (London : ISTE ; Hoboken, N.J. : Wiley, 2012)
Multimodal transport network customers need to be directed during their travels. A travel support tool can be offered by a Multimodal Information System (MIS), which allows them to input their needs and provides them with the appropriate responses to improve their travel conditions. The goal of this book is to design and develop methodologies in order to realize a MIS tool which can ensure permanent multimodal information availability before and during travel, considering passengers' mobility. The authors propose methods and tools that help transport network customers to formulate.
Agent-oriented road traffic simulation -- An agent-based information system for searching and composing mobility aiding services -- Inter-vehicle services and communication -- Modeling and control of traffic flow -- Criteria and methods of evaluation of interactive systems : application to a regulation post in the transport domain.
Includes bibliographical references and index.
Print version record.
Keywords: Transportation engineering; BUSINESS & ECONOMICS -- Industries -- Transportation; TRANSPORTATION -- Public Transportation; Transportation engineering; Electronic books